2017
DOI: 10.1002/sdtp.12051
|View full text |Cite
|
Sign up to set email alerts
|

P‐151: Fast Flexoelectro‐optic Response of Bimesogen‐doped Polymer Stabilized Cholesteric Liquid Crystals in Vertical Standing Helix Mode

Abstract: We experimentally demonstrate fast flexoelectrooptic switching in a liquid crystal cell containing bimesogendoped and polymer-stabilized cholesteric. The device exhibits a response time of less than 0.7 ms and with low hysteresis and color dispersion which is suitable for potential applicationsincluding field-sequential color displays. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…While the flexoelectric response in CB n CB bimesogens has received widespread attention, there is a dearth of systematic experimental demonstrations of commercial device applications due to their high temperature nematic phases which makes it difficult to operate under ambient conditions. Here, we report the experimental demonstration of a swinging phenomenon in CLCs doped with CB7CB, CB9CB, and CB11CB with helical axis normal to the surface and an in‐plane electric field at room temperature, implementing the electrode structure and configuration of CLC that were reported previously . The low frequency electro‐optical switching observed under a microscope provides a direct experimental evidence of a two‐way swinging effect, analogous to a metronome.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…While the flexoelectric response in CB n CB bimesogens has received widespread attention, there is a dearth of systematic experimental demonstrations of commercial device applications due to their high temperature nematic phases which makes it difficult to operate under ambient conditions. Here, we report the experimental demonstration of a swinging phenomenon in CLCs doped with CB7CB, CB9CB, and CB11CB with helical axis normal to the surface and an in‐plane electric field at room temperature, implementing the electrode structure and configuration of CLC that were reported previously . The low frequency electro‐optical switching observed under a microscope provides a direct experimental evidence of a two‐way swinging effect, analogous to a metronome.…”
supporting
confidence: 56%
“…A sub‐millisecond response time is the main attribute of the flexoelectro‐optic behavior of a PSCLC which makes it optimal for the next‐generation electro‐optic and photonic devices . Hence, the main goal of this work is to explore the practical applications of the PSCLC cells to be operated in ambient conditions.…”
mentioning
confidence: 99%
“…They could also measure the flexoelectric parameters in the bimesogenic CLC mixture that was fabricated to exhibit optimized flexoelectric effect. Joshi et al have recently reported fast flexoelectro‐optic response in a polymer stabilized planar CLC doped with bent‐shaped bimesogen compounds . Electrooptical devices fabricated with the polymer stabilized planar texture using in‐plane switching driving scheme displayed fast response, low hysteresis, and color dispersion which renders them as potential candidates for field‐sequential color displays.…”
Section: Uniform Lying Helix Structurementioning
confidence: 99%
“…However, there is another important EO effect called flexoelectric effect in a HTN cell. Some bimesogenic [54][55][56][57]60] and bent-core [58] LC materials with strong flexoelectric effect can be doped into USH precursors as well [71,72]. We injected the USH precursors into an IPS cell, as figure 1(e) illustrates.…”
Section: Sample Preparationmentioning
confidence: 99%